2009
DOI: 10.1200/jco.2008.17.9432
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Prediction in Pediatric Medulloblastoma Based on DNA Copy-Number Aberrations of Chromosomes 6q and 17q and the MYC and MYCN Loci

Abstract: Genomic aberrations in medulloblastoma are powerful independent markers of disease progression and survival. By adding genomic markers to established clinical and histologic variables, outcome prediction can be substantially improved. Because the analyses can be conducted on routine paraffin-embedded material, it will be especially feasible to use this novel molecular staging system in large multicenter clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
232
2
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 273 publications
(250 citation statements)
references
References 33 publications
10
232
2
6
Order By: Relevance
“…Copy number abnormalities of chromosome 17 isodicentric, isochromosome of chromosome 17q, loss of 17p, or gain of 17q are the most frequent chromosomal abnormality in medulloblastomas (Mitelman database 2011, Aldosari et al 2002McCabe et al 2006) it is found in 30-50% of the studied cases (Reardon et al 1997). Isochromosome -isodicentric chromosome 17 is present in approximately one third of the tumors and in some cases is the only chromosomal aberration (Mitelman database 2011;Pfister et al 2009;Ricket and Paulus 2004). It has been observed in 25-30% of childhood MB.…”
Section: Chromosomal Aberration and Its Corroletion To Clinicohistopamentioning
confidence: 99%
See 2 more Smart Citations
“…Copy number abnormalities of chromosome 17 isodicentric, isochromosome of chromosome 17q, loss of 17p, or gain of 17q are the most frequent chromosomal abnormality in medulloblastomas (Mitelman database 2011, Aldosari et al 2002McCabe et al 2006) it is found in 30-50% of the studied cases (Reardon et al 1997). Isochromosome -isodicentric chromosome 17 is present in approximately one third of the tumors and in some cases is the only chromosomal aberration (Mitelman database 2011;Pfister et al 2009;Ricket and Paulus 2004). It has been observed in 25-30% of childhood MB.…”
Section: Chromosomal Aberration and Its Corroletion To Clinicohistopamentioning
confidence: 99%
“…The controversial evidence based mainly on the findings of i(17q) also in Wnt pathway subgroup which in consensus considered as a favorable outcome. The question whether to consider copy number abnormality of chromosome 17 as a marker for poor prognosis and to exclude those found to be Wnt pathway, is still in debate (Pan et al 2005;Pfister et al 2009). Using more sophisticated and advanced techniques such as CGH to profile a panel of 27 primary MB (Reardon et al 1997) revealed frequent loss of 10q, 11, 16q, 17p, and 8p as well as recurrent gains of chromosomes 7, and 17q.…”
Section: Chromosomal Aberration and Its Corroletion To Clinicohistopamentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the aggressiveness and response to therapy can vary considerably between cases, with approximately 30 % of patients dying within 2 years from diagnosis (Pfister et al 2009). The quality of life in long-term survivors is another major issue, because most surviving children have devastating neurologic and cognitive sequelaes (Finlay et al 2007;Packer and Vezina 2008;Pfister et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Some recurrent chromosomal changes have been recently reported to predict survival in MB patients including loss of 17p (Batra et al 1995;Lamont et al 2004), gain of 17q (Pfister et al 2009), presence of an isodicentric chromosome 17 (idic(17)(p11.2)) (Lamont et al 2004;Pan et al 2005), gain of 1q (Lo et al 2007) and monosomy 6 (Thompson et al 2006).…”
Section: Introductionmentioning
confidence: 99%